Effect of antileukotriene treatment on capsular contracture: an experimental study - Cristina Pires Camargo; Heloisa Andrade Carvalho; Marcia Saldanha Kubrusly; Sofia Amaral Medeiros; Julio Morais Besteiro; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: 40% of patients undergoing radiotherapy after breast reconstruction by silicone prosthesis implant may develop prosthesis encapsulation. Several strategies have already been tested to prevent capsule contracture with unsatisfactory results. This study analyzed the effect of topical antileukotriene (AL) on capsular contracture formation in rats with silicone implants associated with irradiation. Methods: Silicone blocks were implanted in the dorsal region in 20 female rats Wistar with weights ranging from 200-250g. The animals were divided into two groups: control (injection of 0.9% saline solution into the tissue around the implant) and intervention group (injection of 10mg of AL into the tissue around the implant). Immediately after surgery, the animals were irradiated with a single dose of 10Gy. After two months, we collected capsule samples for histological analysis and gene expression analysis of the following biomarkers: iNOS, VEGF-a and MMP-9. Results: Vascular density was lower in the AL group when compared to the control group (55.4±30.0 vs. 81.8±26.7, p=0.05, respectively). Similarly, VEGF-a had the same behavior (control group - 0.34±0.1 vs. group Al - 0.02±0.001, p=0.04). Conclusion: This study suggested that treatment with AL decreases angiogenesis in animals submitted to silicone implants and underwent radiotherapy.